Manefiesto del rey don Iñigo Ariesta a los navarros (1868) - García-Sanz Marcotegui, Ángel (Huarte de San Juan. Geografía e Historia, 2006)
This is about a very curious document from the end of 1868, which was writen in a figuratively medieval language. From a historicist perspective, its author, a lawyer attached to the Liberals, called Cayo Escudero Marichalar, makes some statements and proposals about the situation of Navarre at that time. The jocular, humorous tone, which the uses, makes it difficult to get to know his final intention exactly, but what is obvious is his interest in emmphasizing the danger in which the privileged Regional Charter (Fueros) would be, if a return to the situation before the Ley de 16 de agosto de 1841 (Law of 16 August 1841) was claimed.